Processing Mandarin Tone 3 Sandhi at the Morphosyntactic Interface: Reduplication and Lexical Compounds - Gao, Feier; Lyu, Siqi; Lin, Chien-Jer Charles (Frontiers in Psychology, 2021)
Mandarin tone 3 sandhi is a phonological alternation in which the initial tone 3 (i.e., low tone) syllable changes to a tone 2 (i.e., rising tone) when followed by another tone 3. The present study used a cross-modal syllable-morpheme matching experiment to examine how native speakers process the sandhi sequences derived from verb reduplication and compounding, respectively. Embedded in a visually-presented sentential context, a disyllabic sequence containing a sandhi target was displayed simultaneously with a monosyllabic audio, either a tone 1 (i.e., high-level tone), tone 2 (i.e., rising tone) or tone 3 (i.e., low tone), and participants judged whether the audio syllable matched with the visual morpheme. Results showed that the tone 3 sandhi was processed differently in the two constructions. The underlying and the surface tone were co-activated and competed with each other in sandhi compounds whereas predominant activation of the underlying tone, over the surface tone, was observed in reduplication. The processing of tone 3 sandhi offers support for distinctive morphological structures: a lexical compound is represented both as a whole-word unit and as a combination of two individual morphemes whereas a verb reduplication is represented and accessed as a monomorphemic unit in the mental lexicon.